Overview of Factors That Encourage Interest in Implant Contraception with the Reasoned Action Theory Approach in Non Implant Contraceptive Acceptor (In Polindes Sumekar Kapu Village, Merakurak District, Tuban Regency - erna eka wijayanti (Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2019)
Today there are still many mothers who are not interested in joining Family Planning (KB). This lack of interest is due to many acceptors who are afraid of minor surgical wounds done during installation, incorrect information about implant contraceptives and lack of family support. In addition, there are other factors that cause low Mother's interest for KB Implant attitude and subjective norms. The purpose of this study is to know the description of factors that encourage interest for KB Implant With Reasoned Action Theory Approach In Non-Implant Family Planning Acceptor At Polindes Sumekar Kapu Village, Merakurak Sub-district, Tuban Regency